Global Surgery Fellowships—An Investigation of Opportunities, Outcomes, and Applicants - Davison, Eliza J.; Singh, Satyendra K.; Jemec, Barbara (Journal of Hand and Microsurgery, 2021)
Following the Lancet Commission on Global Surgery in 2015, the Global Surgery Fellowships have risen in popularity, advertised as formalized opportunities for surgical trainees who have an interest in international surgical care. There is currently no up-to-date review of all fellowships available and an urgently needed overview of these opportunities is presented, including critical appraisal of their accessibility, funding, and outcomes. Detailed searches were conducted on the web engine Google, using the term “global surgery fellowship” and iterations. From the 547 resulting links, after applying exclusion criteria, 69 relevant fellowships were included in analysis. The majority of fellowships based in the United States (55%) and arranged by non-governmental organizations (NGOs) or universities (>70%). Also, 60% of fellowships had a duration of 1 year or longer. Only a quarter of the fellowships was open solely to trainees from low- or middle-income countries (LMIC), with over 80% of these being full funded. But 40% of the fellowships were advertised as open to trainees from any country, though only one-third of these provided full funding. Key themes across the fellowships’ outcomes included “Professional Development,” “Research,” and “LMIC Quality Improvement.” Almost all of the fellowships (95%) stated international travel opportunities. Twelve of the fellowships offered higher degrees, with the most common being a Masters of Public Health. The global distribution of fellowships and reduced funding opportunities for trainees from LMIC limit accessibility of the Global Surgery Fellowships. It is, however, still promising that most of key themes and high rates of international work are in line with The Lancet Commission’s recommendations. This overview of the Global Surgery Fellowships highlights the need for collaboration between institutions and has illustrated points for consideration when introducing new and the value of established fellowships.
Keywords: global surgery; surgery fellowships; international hand surgery; international microsurgery; surgical education